Maintenance of Hydration in "Post-Coronary" Marathon Runners. Issue 3 (October 1975) - Kavanagh, T.; Shephard, R. J.
Abstract : Three post-coronary patients participated in the Hawaiian Marathon race in December 1973, covering the 26¼ miles in 250-259 minutes at an average speed of 6.1-6.3 mph. Preloading with 850 ml. of a proprietary electrolyte/glucose solution "Erg", and further 300 ml. drinks of the same fluid every 30 min. were sufficient to maintain a state of hyperhydration, as evidenced both by calculations of water balance and objective measures of red cell count and haematocrit; it is argued that substantial dehydration need not be incurred even in younger runners with much higher sweat rates. The "Erg" preparation provided good stabilisation of plasma sodium ion concentrations, but potassium ions rose by the end of the race. Substantial increments of L.D.H. and S.G.O.T. persisted three hours after a race, making a careful exercise history important to the diagnosis of myocardial infarction. Glucose levels had reached the lower limit of normal by the end of the race, and rises of blood urea suggested some protein catabolism; however, cholesterol levels remained substantially unchanged. A small increase of blood bilirubin was noted during and after the race.